The Application of Restorative Justice in Juvenile Delinquency - Amara, Amara (Journal of Legal Studies and Researches, 2026)
Restorative justice is an important modern approach to ending criminal prosecution and resolving public lawsuits friendly through mechanisms and procedures carried out by the competent judicial authorities. Legislation has moved to regulate restorative justice through legal texts and apply it to certain crimes eventually extending it to offenses committed by juveniles. This focuses on juveniles' rehabilitation and reintegration into society.